Dissecting Neuronal Activation on a Brain-Wide Scale With Immediate Early Genes - Franceschini, Alessandra; Costantini, Irene; Pavone, Francesco S.; Silvestri, Ludovico (Frontiers in Neuroscience, 2020)
Visualizing neuronal activation on a brain-wide scale yet with cellular resolution is a fundamental technical challenge for neuroscience. This would enable analyzing how different neuronal circuits are disrupted in pathology and how they could be rescued by pharmacological treatments. Although this goal would have appeared visionary a decade ago, recent technological advances make it eventually feasible. Here, we review the latest developments in the fields of genetics, sample preparation, imaging and image analysis that could be combined to afford whole-brain cell-resolution activation mapping. We show how the different biochemical and optical methods have been coupled to study neuronal circuits at different spatial and temporal scales, and with cell-type specificity. The inventory of techniques presented here could be useful to find the tools best suited for a specific experiment. We envision that in the next years mapping of neuronal activation could become routine in many laboratories, allowing dissecting the neuronal counterpart of behavior.